Translating complex climate science into practical agro-climate advisories for 13-15 million smallholder farmers in Ethiopia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Creation of Ethiopia’s digital agro-climate advisory platform, a collaborative partnership between government institutions and CGIAR centers, represents a breakthrough in providing climate-information and timely decision-support tools to smallholder farmers to strengthen adaptive capacity and resilience. Partnership between Ministry of Agriculture and EDACaP team with Ethiopia’s FANA Broadcasting Corporate led to dissemination of agro-climate messages to 13-15 million smallholder farmers across FANA’s 11 regional broadcasting centers in Ethiopia. Information used for planning farming activities for season taking into consideration climate-related risks.